MRI-detected residual retropharyngeal lymph node after intensity-modulated radiotherapy in nasopharyngeal carcinoma: Prognostic value and a nomogram for the pretherapy prediction of it. (April 2020) - Li, Wang-Zhong; Liu, Guo-Ying; Lin, Lan-Feng; Lv, Shu-Hui; Qiang, Meng-Yun; Lv, Xing; Wu, Yi-Shan; Liang, Hu; Ke, Liang-Ru; Wang, De-Ling; Yu, Ya-Hui; Qiu, Wen-Ze; et al.
Highlights: MRI-detected residual retropharyngeal lymph node significantly affects NPC survival outcomes. We construct an easy-to-use tool for the pretherapy prediction of retropharyngeal lymph node. The pretherapy prediction of residual retropharyngeal lymph node may facilitate clinical decision making. Abstract: Background and purpose: To evaluate the prognostic value of MRI-detected residual retropharyngeal lymph node (RRLN) at three months after intensity-modulated radiotherapy (IMRT) in patients with nasopharyngeal carcinoma (NPC) and second, to establish a nomogram for the pretherapy prediction of RRLN. Materials and methods: We included 1103 patients with NPC from two hospitals (Sun Yat-Sen University Cancer Center [SYSUCC, n = 901] and Dongguan People's Hospital [DGPH, n = 202]). We evaluated the prognostic value of RRLN using Cox regression model in SYSUCC cohort. We developed a nomogram for the pretherapy prediction of RRLN using logistic regression model in SYSUCC training cohort ( n = 645). We assessed the performance of this nomogram in an internal validation cohort (SYSUCC validation cohort, n = 256) and an external independent cohort (DGPH validation cohort, n = 202). Results: RRLN was an independent prognostic factor for OS (HR 2.08, 95% CI 1.32–3.29), DFS (HR 2.45, 95% CI 1.75–3.42), DMFS (HR 3.31, 95% CI 2.15–5.09), and LRRFS (HR 3.04, 95% CI 1.70–5.42). We developed a nomogram based on baseline Epstein–Barr virus DNA level and three RLN status-related features (including minimum axial diameter, extracapsular nodal spread, and laterality) that predicted an individual's risk of RRLN. Our nomogram showed good discrimination in the training cohort (C-index = 0.763). The favorable performance of this nomogram was confirmed in the internal and external validation cohorts. Conclusion: MRI-detected RRLN at three months after IMRT was an unfavorable prognostic factor for patients with NPC. We developed and validated an easy-to-use nomogram for the pretherapy prediction of RRLN.